2022
DOI: 10.1155/2022/8349448
|View full text |Cite|
|
Sign up to set email alerts
|

Analyzing the Effect of Badminton on Physical Health and Emotion Recognition on the account of Smart Sensors

Abstract: Emotional ability is an important symbol of human intelligence. Human’s understanding of emotions, from subjective consciousness to continuous or discrete emotional dimensions, and then to physiological separability, has shown a trend of gradually diverging from psychological research to the field of intelligent human-computer interaction. This article is aimed at studying the effects of smart sensor-based emotion recognition technology and badminton on physical health. It proposes a method of using smart sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…They used the hand motion signals generated during writing to detect emotional states, but this is not friendly to longterm data monitoring under different writing habits. Chang et al [24] used intelligent inertial sensors to identify emotions during badminton movement, and sensors can respond to emotional changes, such as happiness, nausea, and sadness. However, with the increase of exercise time, the degree of physical fatigue affects the recognition effect of emotion.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They used the hand motion signals generated during writing to detect emotional states, but this is not friendly to longterm data monitoring under different writing habits. Chang et al [24] used intelligent inertial sensors to identify emotions during badminton movement, and sensors can respond to emotional changes, such as happiness, nausea, and sadness. However, with the increase of exercise time, the degree of physical fatigue affects the recognition effect of emotion.…”
Section: Related Workmentioning
confidence: 99%
“…Chang et al. [24] used intelligent inertial sensors to identify emotions during badminton movement, and sensors can respond to emotional changes, such as happiness, nausea, and sadness. However, with the increase of exercise time, the degree of physical fatigue affects the recognition effect of emotion.…”
Section: Related Workmentioning
confidence: 99%
“…Research about factors influencing badminton athletes' performance at the international level underscores the sport's complexity, encompassing interrelated elements. Notably, studies by [1,2] emphasize physical factors such as strength, flexibility, and speed in chasing the shuttlecock. The technical and tactical aspects highlighted by [3,4], including mastery of basic techniques and strategic prowess, also prove crucial for success in competitive badminton.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%